Pengembangan Modul Kerja Bengkel dan Gambar Teknik untuk Sekolah Menengah Kejuruan - Shandy Oktafianto Pratama; Muldi Yuhendri (Jurnal Pendidikan Teknik Elektro, 2020)
Distance learning carried out during the COVID 19 pandemic requires learning materials that students can use independently. One of the learning sources that can be used independently is the learning module. This study proposes the development of a workshop work subject module and technical drawings for class X Audio Video Engineering students at the State Vocational High School (SMKN) 1 Koto XI Tarusan. Module development is carried out using the 4D method (define, design, develop, and disseminate). Using the 4D development method can make students better understand and know how to use workshop work learning modules and technical drawings. To see the feasibility of the module, a validity test was carried out by an expert and a practicality test by the user. The test results gave the validity value carried out by the validator of 0.89 in the valid category, while the practicality test carried out by the teacher of workshop work subjects and technical drawings gave a value of 87.14% with the practical category. The results of this study indicate that the learning modules made for workshop work subjects and technical drawings are suitable for use as learning resources.